2021
DOI: 10.1200/jco.2021.39.3_suppl.172
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sociodemographic characteristics on gastric cancer outcomes: A retrospective review of a large single center study.

Abstract: 172 Background: Gastric cancer (GC) remains a pervasive condition in the US with high morbidity and mortality. Race/ethnicity, lack of insurance, and poverty may all be contributing to this burden, especially in select populations. We evaluated the impact of these sociodemographic factors on GC outcomes at a hospital with high immigrant-patient populations. Methods: We conducted a retrospective study to identify patients diagnosed with GC between year 2010 and 2019. Data obtained from our institution database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Findakly et al conducted a large single-institution retrospective cohort study evaluating the impact of sociodemographic characteristics on GC outcomes among 111 patients with GC, demonstrating that lack of insurance or having Medicaid were associated with significantly worse survival outcomes. 20 However, most of the patients in the study were uninsured, where fewer than 30% of them had any form of insurance. Another study by Jang et al, aimed to evaluate the association of medical insurance status of 333 Korean patients with GC and their survival after gastrectomy, reporting that the medical aid group had a similar survival rate compared to the Medicaid/Uninsured group.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Findakly et al conducted a large single-institution retrospective cohort study evaluating the impact of sociodemographic characteristics on GC outcomes among 111 patients with GC, demonstrating that lack of insurance or having Medicaid were associated with significantly worse survival outcomes. 20 However, most of the patients in the study were uninsured, where fewer than 30% of them had any form of insurance. Another study by Jang et al, aimed to evaluate the association of medical insurance status of 333 Korean patients with GC and their survival after gastrectomy, reporting that the medical aid group had a similar survival rate compared to the Medicaid/Uninsured group.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research on the association of insurance status and GC outcomes have shown worse survival outcomes while others have documented no difference in the rate of survival. [19][20][21] However, the sample sizes of these studies may not have been adequately powered to confidently assert these conclusions. In addition, none of these studies focused on the worst histologic type of GC, gastric adenocarcinoma.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the Netherlands, younger age and higher socioeconomic status (SES) were independent factors for receiving treatment in patients with esophageal and gastric cancer [ 38 , 39 ]. Notably, patients with gastric cancer who lack insurance have been shown to have worse survival outcomes and receive less therapy compared to insured patients [ 40 , 41 ]. Insurance status plays a role in the type of treatment patients can receive (as well as where they can receive it).…”
Section: Discussionmentioning
confidence: 99%